Arte y arqueología medievales de Aragón en el Museo Arqueológico Nacional - Franco, Ángela (Artigrama, 2005)
En el presente artículo se analiza la documentación relativa a los objetos medievales de variado carácter, procedentes de Aragón e ingresados en el Museo Arqueológico Nacional desde su creación hasta fechas recientes. El conjunto más importante proviene de las gestiones del comisionado D. Paulino Savirón y Estevan, que desempeñó su labor con entusiasmo y dedicación durante los años comprendidos entre 1866 y 1873, recorriendo las provincias de Zaragoza, Huesca y Teruel. Posteriormente los ingresos fueron más espaciados y en cantidad reducida. El conjunto de arte y arqueología aragoneses ocupan entre las colecciones del Museo Arqueológico Nacional un lugar muy destacado. This article analyses the documentation related to mediaeval objects of diverse nature which were brought from Aragon to the Museo Arqueológico Nacional. Some of these objects were incorporated into the collection at the time of the foundation of the Museo, while some pieces have arrived in more recent times. The most important group is due to the negotiations of the commissioner D.Paulino Saviron y Estevan, whose dedication and enthusiasm during the period 1866-1873 compelled him to travel around the provinces of Zaragoza, Huesca, and Teruel. Further additions to the collection after this became few and far between. The set of Aragonese Art and Arqueology hold an outstanding place among the collections of the Museo Arqueologico Nacional.